Isolation of a manganese binding protein from mouse liver - Bonilla, Ernesto (Investigación Clínica, 2013)
A manganese-binding protein with mol. wt. of approx. 71.000 has been identified in the membranous fractions of mouse liver. This protein seems to have characteristics similar to transferrin.